Drucebo effect in statin therapy: more attributable to the patient, the doctor, or the mass media?. (3rd October 2022) - Cosmi, D; D'Orazio, S; Mariottoni, B; Tarquini, B; Cosmi, F
Abstract:  : In recent years, the term "drucebo effect" (drug + nocebo) has been coined to mean the nocebo effect attributable more to the patient's expectations, the doctor's preferences and the interference of the mass media rather than the actual pharmacological effect [1, 2]. We evaluated this effect over the last 10 years in 9, 605 outpatients treated with statins, in primary (27%) and secondary (73%) prevention. Statin intolerance was reported in 1, 729 patients (18%) with discontinuation of therapy for 5 days to 4 weeks. The table shows the causes of the presumed intolerance. In patients with muscular symptoms we calculated the related SMIS (Statin Myalgia Index Score) [3]. Patients with myalgia with or without CPK elevation and probable or possible SMIS were advised to halve the statin dose and reassess after 2–4 weeks. With persisting symptoms, the statin was changed. If symptoms persisted also with the second statin, the patient was advised to take the drug every other day. In case of unlikely SMIS, the decision to resume statin therapy was shared with the patients, with an accurate counseling, informing them of the important benefits of statins regarding mortality and morbidity. Probable true statin intolerance was found in 576 patients (6% of the overall statin therapy population: 332 with myalgia with or without CPK elevation and SMIS probable, 152 with myalgia and CPK elevation with SMIS possible, 46 with asymptomatic elevation of CPK, 15 transaminases increase, 21 with general malaise, 10 with severe depression). In 12% of patients, on the other hand, the interruption is attributable to a nocebo effect due both to the patient and both to the treating physician or other specialist, inclined to attribute the unwanted symptoms more to the drug than to other factors or to consider it non-modifiable by changing statin or doses. The Influence of the mass media is significant, too, and it is difficult to distinguish a greater responsibility of one or the other. Conclusions: in patients treated with statins a drucebo effect is attributable in part to the patient, in part to the doctor and to the mass media, which tend to attribute the symptoms (especially of muscle origin) to the treatment and to interrupt the therapy without take into account the clear benefits regarding reduction of mortality and morbidity [4]. In our study, a probable true intolerance to statins is found in about one third of patients who report symptoms of a presumed intolerance. Funding Acknowledgement: Type of funding sources: None.